2021
DOI: 10.1007/s10143-021-01711-1
|View full text |Cite
|
Sign up to set email alerts
|

Neuropathological interpretation of stimulated Raman histology images of brain and spine tumors: part B

Abstract: Intraoperative histopathological examinations are routinely performed to provide neurosurgeons with information about the entity of tumor tissue. Here, we quantified the neuropathological interpretability of stimulated Raman histology (SRH) acquired using a Raman laser imaging system in a routine clinical setting without any specialized training or prior experience. Stimulated Raman scattering microscopy was performed on 117 samples of pathological tissue from 73 cases of brain and spine tumor surgeries. A boa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 26 publications
0
16
0
Order By: Relevance
“…Similarly, Straehle et al described good neuropathological interpretability of SRH images for approximately 96% of cases included in a cohort of different CNS tumors. 4 According to neuropathological judgment, a histopathological diagnosis could be made for 92 of 94 (98%) cases on the basis of the SRH images in our study; in contrast, a histopathological diagnosis could not be obtained in 2 of our SRH images. Interestingly, both SRH images were acquired during resection of a lesion with a final histopathological diagnosis of cavernoma based on H&E images.…”
Section: Discussionmentioning
confidence: 56%
See 3 more Smart Citations
“…Similarly, Straehle et al described good neuropathological interpretability of SRH images for approximately 96% of cases included in a cohort of different CNS tumors. 4 According to neuropathological judgment, a histopathological diagnosis could be made for 92 of 94 (98%) cases on the basis of the SRH images in our study; in contrast, a histopathological diagnosis could not be obtained in 2 of our SRH images. Interestingly, both SRH images were acquired during resection of a lesion with a final histopathological diagnosis of cavernoma based on H&E images.…”
Section: Discussionmentioning
confidence: 56%
“…In the literature, the study by Straehle et al reported a diagnostic accuracy of 100% for SRH used to diagnose LGG and, interestingly, cerebral or spinal metastases. 4 However, the authors found a lower diagnostic accuracy of 88.9% for SRH when used to diagnose HGG and meningiomas (90.9%). 4 According to our data and the findings reported in the literature, the SRH technique is capable of visualizing the histopathological characteristics of suspected CNS tumors during surgery with an image quality comparable to that of conventional H&E images, which is generally accessible days after surgery during routine neuropathological workup.…”
Section: Diagnostic Accuracy Of Srh Compared With Hande Imagesmentioning
confidence: 90%
See 2 more Smart Citations
“…During the first experiments, they had to improve process optimization regarding the tissue treatment; nevertheless, it was easily implemented in the surgical workflow in a “plug-and-play” manner [ 44 ]. In a second study, the same team quantified the neuropathological interpretability in a routine clinical setting without specialized training [ 61 ]. They tested the device on 117 samples of pathological tissue from 73 patients and a neuropathologist assessed image quality by scoring subjective tumor infiltration and stated a diagnosis based on the SRH images.…”
Section: Innovations To Increase Biopsy Diagnostic Yieldmentioning
confidence: 99%